Legal Standing Issues in Mixed Marriage Disputes and Their Implications for Legal Certainty (A Study of Decision Number 521/PDT/2020/PT.DKI) - Najwa Alicia Yasmin B; Marsya Keisya Gunawan; Voleta Istiqomah; Dwi Desi Yayi Tarina (Media Hukum Indonesia (MHI), 2026)
Mixed marriages raise numerous legal issues, particularly regarding legal certainty and legal standing in civil disputes. The purpose of this study is to evaluate the legal status of Decision No. 521/PDT/2020/PT.DKI and how it impacts the legal protection of the parties. Statutory regulations and case studies are the normative legal methods used in this research. The discussion reveals that the lawsuit was rejected due to a lack of legal standing and formal defects, primarily due to the delayed registration of the marriage abroad. This situation demonstrates the dominance of a formal approach in judicial practice, which diminishes substantive justice. As a result, the civil rights of parties in mixed marriages are not adequately protected and legal uncertainty exists. Consequently, to provide fairer and more certain protection for each party, regulatory improvements and harmonization are needed.